Development of a custom-made 2.8 T permanent-magnet dipole photon source for the ROCK beamline at SOLEIL - Pascale Brunelle; Nicolas Béchu; Valérie Briois; Fabrice Marteau; Marc Ribbens; Philippe Berteaud; Xavier Delétoille; Eric Dupuy; Christian Herbeaux; Marie Labat; Alain Lestrade; Amor Nadji; et al. (Journal of Synchrotron Radiation, 2023)
In August 2021, the SOLEIL storage ring was restarted after the summer shutdown with a new bending magnet made entirely of permanent magnets. Producing a magnetic field of 2.8 T, it replaced one of the 32 electromagnetic dipoles (magnetic field of 1.7 T) of the ring to allow the ROCK beamline to exploit more intense photon fluxes in the hard X-ray range, thus improving the time resolution performances of the beamline for experiments carried out above 20 keV. The reduction of the new dipole magnetic gap required to produce the higher field has led to the construction and installation of a new vacuum vessel. The realization of the new dipole with permanent magnets was a technological feat due to the very strong magnetic forces. The permanent-magnet assembly required dedicated tools to be designed and constructed. Thanks to accurate magnetic measurements, a precise modelization of the new dipole was performed to identify its effects on the electron beam dynamics. The first measurements carried out on the ROCK beamline have highlighted the expected increase in photon flux, and the operation performances remain unchanged for the other beamlines. Here, the major developments and results of this innovative project are described in terms of technology, electron beam dynamics and photon beam performance on the ROCK beamline.